Impact of timing and setting of palliative care referral on quality of end‐of‐life care in cancer patients - Hui, David; Kim, Sun Hyun; Roquemore, Joyce; Dev, Rony; Chisholm, Gary; Bruera, Eduardo (Cancer, 2014)
BACKGROUND Limited data are available on how the timing and setting of palliative care (PC) referral can affect end‐of‐life care. In this retrospective cohort study, the authors examined how the timing and setting of PC referral were associated with the quality of end‐of‐life care. METHODS All adult patients residing in the Houston area who died of advanced cancer between September 1, 2009 and February 28, 2010 and had a PC consultation were included. Data were retrieved on PC referral and quality of end‐of‐life care indicators. RESULTS Among 366 decedents, 120 (33%) had an early PC referral (>3 months before death), and 169 (46%) were first seen as outpatients. Earlier PC referral was associated with fewer emergency room visits (39% vs 68%; P < .001), fewer hospitalizations (48% vs 81%; P < .003), and fewer hospital deaths (17% vs 31%; P = .004) in the last 30 days of life. Similarly, outpatient PC referral was associated with fewer emergency room visits (48% vs 68%; P < .001), fewer hospital admissions (52% vs 86%; P < .001), fewer hospital deaths (18% vs 34%; P = .001), and fewer intensive care unit admissions (4% vs 14%; P = .001). In multivariate analysis, outpatient PC referral (odds ratio [OR], 0.42; 95% confidence interval [CI], 0.28‐0.66; P < .001) was independently associated with less aggressive end‐of‐life care. Men (OR, 1.63; 95% CI, 1.06‐2.50; P = .03) and hematologic malignancies (OR, 2.57; 95% CI, 1.18‐5.59; P = .02) were associated with more aggressive end‐of‐life care. CONCLUSIONS Patients who were referred to outpatient PC had improved end‐of‐life care compared with those who received inpatient PC. The current findings support the need to increase the availability of PC clinics and to streamline the process of early referral. Cancer 2014;120:1743–1749. © 2014 American Cancer Society. In this retrospective cohort study, patients with advanced cancer who have early access to outpatient palliative care receive less aggressive care at the end of life compared with those who have delayed access to palliative care and those who receive inpatient palliative care. These findings support the need to increase the availability of palliative care clinics and to streamline the process of early referral.